RICE PRODUCTION IN UTTAR PRADESH: GROWTH, INSTABILITY AND DECOMPOSITION ANALYSIS - PARVAT SINGH (The Journal of Research ANGRAU, 2025)
The present study investigated the association between growth rate and instability regarding to the production, area and yield of rice in Uttar Pradesh. The data was extracted from the (Directorate of Economics and Statistics, DES), Department of Agriculture and Farmers Welfare, (MoA, GoI), spanning from 1990-91 to 2021-22. The data has been segmented into four periods for analysis. The compound annual growth rate, Coppock’s and Cuddy-Della Valle Instability Index have been estimated for the four periods.The growth rate analysis showed the rice crops for the area (0.56%), production (1.30%) and productivity (1.4%) overall, respectively. The highlights of the overall instability measures result of the CDVI Index in rice were observed to be low under area (4.09%) and low (9.59%) instability in production, respectively. In terms of Coppock’s performed measure of instability was registered to be low (38.42%) under area cultivation and medium (42.93%) in the production, respectively. The results from the decomposition analysis revealed that the yieldeffect contributed the highest in production observed during period II (155.56%), which shows that there is a negative in-area effect (-65.56%), and an interaction effect was observed (7.78%). The study suggests that production should be prioritized and improving productivity to reach the future demand for rice; it also indicates that there is further potential for the enhancing production of rice in Uttar Pradesh by the adoption of advanced inputs technology.